Penerapan Metode Importance Performance Analysis (IPA) terhadap Tingkat Kepuasan Nasabah pada PT. Bank Central Asia Tbk Berbasis Android - M. Akbar; Faisal Amir Harahap (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
PT. Bank Central Asia Tbk KCP Pulo Brayan is one of the branches that has many customers in carrying out transactions according to customer needs. One of the missions of PT Bank Central Asia Tbk KCP Pulo Brayan is to understand customer needs and provide support services to achieve optimal levels of customer satisfaction. The assessment of the level of customer satisfaction of each branch is carried out by the head office by conducting random telephone calls to customers who transact at KCP Pulo Brayan. The weakness of the assessment system is the lack of transparency of the results of customer satisfaction assessments conducted by the head office to the KCP Pulo Brayan office. KCP Pulo Brayan is still not optimal in service evaluation so that the evaluation results from customer assessments are still considered very lacking by the head office. To overcome this problem, PT. Bank Central Asia Tbk KCP Pulo Brayan requires a system to determine the level of customer satisfaction. The system developed uses a questionnaire filled out by customers with Android devices. The result of the customer satisfaction level system is an application system designed based on Android for the customer service system at KCP Pulo Brayan with the application of the Importance Performance Analysis (IPA) method. The application of this method aims to identify service attributes that need primary attention, as well as being the basis for providing recommendations to improve overall service quality.